Modernisasi dan Pembaharuan; Analisis Epistemologi Ilmu Islam Klasik dan Kontemporer - Nazar Naamy (LP2M STIT Palapa Nusantara, 2023)
Through Hassan Hanafi's theological and intellectual reconstruction, this study analyzes the projection of Islamic renewal. He recognized the necessity to recreate classical theology, which was thought to be weakly practical and overly abstract in its description of theological terminology. The author serves as the primary instrument, analyzes the numerous phenomena discovered, and uses Hanafi's writings as source material for the analysis. So that the author may distinguish between empirical reality and focus, elaborate on the empirical reality behind the phenomena, and provide a methodical and factual account of the information regarding the thing to be researched. Some of the results of the analysis found include (1) Hanafi tries to bridge the discourse on classical Islamic sciences which is responsive to the problems of Muslims today. (2) He describes a future civilization that will face a variety of difficulties that the Muslim generation will need to prepare for with useful classical studies. (3) To combat the backwardness of society, which is reflected in progress and enlightened thought, Hanafi cultivates critical thinking. It also builds the capacity to reconstruct reality from negative to positive aspects and to take advantage of current changes for the social benefit of Muslims. (4) Developing classical sciences as an attraction and support in an effort to build a generation that is religious and able to become agents of change in the future.